AAnalysis of the Impact of the Covid 19 Pandemic on Distance Learning at Universitas Dirgantara Marsekal Suryadarma - Cynthia Rahmawati; Jehan Saptia Kurnia (Jurnal Mantik, 2022)
The Covid-19 pandemic had a extraordinary impact on various aspects of life, including aspects of health, humanity, economy, social and education. Therefore, to reduce the impact of the spread of Covid-19 evenly and quickly, health protocols and policies for restricting mobility between regions and between countries are strictly implemented. The world of higher education has changed lectures, thesis guidance and other academic activities that initially used the face-to-face method (offline), now need to be changed to distance learning methods. At Dirgantara Marshal Suryadarma University is required to change the face-to-face learning system to an online system (E-Class) as a result of the COVID-19 pandemic. However, based on the observations of previous researchers, several obstacles were found in the current PJJ system process which is still not effective and efficient as a substitute for formal or face-to-face education. The main purpose of this paper is to further analyze the direct and indirect impacts that have occurred and been caused by the Covid-19 pandemic on distance learning on student satisfaction in higher education, especially at the Industrial Technology Faculty, Dirgantara Marshal Suryadarma University in the academic year. 2020/2021 Even. This study uses quantitative descriptive research methods. Based on the results of the study, it is known that the impact of the pandemic on the distance learning process so far 57.47% of students already have devices, but on the other hand students feel they cannot study independently by 8.14%, and there is an ineffectiveness of PJJ that is felt by students in receiving material learning by 6.79%. This ineffectiveness is caused by several dominant obstacles, among others: constrained by unfavorable environmental conditions (33%), and constrained by unstable internet network (29.9%). The results of this study are expected to assist in the preparation of effective and efficient learning methods, so that students can obtain optimal education in a conducive environment and supported by a stable internet network. For this reason, universities need to review current distance learning methods, and also need to strengthen digital literacy for both students and lecturers.